Editorial: recurrence of Helicobacter pylori infection—still the same after all these years…. Issue 1 (11th December 2017) - Shah, E.; Chey, W. D.
Abstract : Linked Content This article is linked to Hu et al papers. To view these articles visithttps://doi.org/10.1111/apt.14319 andhttps://doi.org/10.1111/apt.14386 .